Genome-Wide Analysis Suggests the Relaxed Purifying Selection Affect the Evolution of WOX Genes in Pyrus bretschneideri, Prunus persica, Prunus mume, and Fragaria vesca - Cao, Yunpeng; Han, Yahui; Meng, Dandan; Li, Guohui; Li, Dahui; Abdullah, Muhammad; Jin, Qing; Lin, Yi; Cai, Yongping (Frontiers in Genetics, 2017)
WUSCHEL-related homeobox (WOX) family is a large group of transcription factors (TFs) specifically found in plants. WOX TFs are known to play important role in plant development and are related to the appearance of evolutionary novelties. Although the roles of WOXs in Arabidopsis and rice have been well studied, however, little are known about the relationships among the main clades in the molecular evolution of these genes in Rosaceae. Here, we carried out a genome-wide analysis and identified 14, 10, 10 and 9 of WOX genes from four Rosaceae species (Fragaria vesca, Prunus persica, Prunus mume and Pyrus bretschneideri, respectively). According to evolutionary analysis, as well as amino acid sequences of their homodomains, these genes were divided into three clades with nine subgroups. Furthermore, due to the conserved structural patterns among these WOX genes, it was proposed that there should exist some highly conserved regions of microsynteny in the four Rosaceae species. Moreover, most of WOX gene pairs were presented with the conserved orientation among syntenic genome regions. In addition, although no significant positive selection was detected according to substitution models analysis using PMAL software, type I functional divergence was found among certain amino acids in WOX proteins. These results revealed that the relaxed purifying selection might be the main driving force during the evolution of WOX genes in the tested Rosaceae species. This study provides useful information for further research on evolution of the WOX genes in family Rosaceae.